Influence de la zone de récolte sur les paramètres biochimiques de Lathyrus sativus (gesse) et conséquences de son incorporation dans l’alimentation de lapin sur la qualité de la viande. - CISSE Aminatou, Mahamadou (My University, 2023)
The grass pea (Lathyrus sativus L.) contains significant levels of protein, thus encouraging its use in both human and animal diets to address protein deficiencies. This study primarily focuses on profiling the primary and secondary metabolites of grass pea from Sidi-Bel-Abbès and Ain Defla, and their antioxidant biological activities. It also investigates the effect of substituting livestock feed with an experimental feed containing 40% grass pea from Sidi-Bel-Abbès on the quality of rabbit meat. Polyphenols were assayed using the Folin Ciocalteu method, proteins using Lowry’s method; as for the antioxidant activity, it was determined by the DPPH radical scavenging method. The assays show a significant difference between the varieties from Ain Defla and Sidi-Bel-Abbès in terms of total polyphenol content, with 1,473±0,015 mg GAE/g DM vs 1,277±0,059 mg GAE/g DM respectively; however, the protein content of the seeds from both sources shows no significant difference, with 23,83±1,415% for the variety from Sidi-Bel-Abbès vs 23,83±1,299% for that from Ain Defla. The antioxidant activity study shows that grass pea extracts have a capacity to trap the DPPH radical, with %IC50 18.60 μg/mL for Sidi-Bel-Abbès and 19,65 μg/mL for Ain Defla. The protein content of the hind legs (thigh) and saddle of rabbits from the 40% batch show significant differences compared to those from the control batch, with 16,51±0,861% and 15,76±1,13% respectively vs 15,95±0,861% and 13,88±0,323% for the control batch. The overall results show that grass pea presents enormous nutritional and economic benefits that could contribute to reducing the import of expensive food.
Keywords: Lathyrus sativus L.; nutritional parameters; food incorporation; rabbit; meat quality